(untitled) (Marketing Journal, 2025)
This study examines the effectiveness of integrating digital technologies – databases, cloud systems, artificial intelligence and other modern tools – into the management processes of higher education institutions. With the help of digital technologies, ad ministrative, financial, academic and scientific management systems of educational institutions can become more transparent, efficient and efficient. These technologies optimize information flows within the institution, facilitate decision - making, improve resource management and allow for individualization of the learning process. Digital management technologies also increase the active participation of students in the learning process, establish effective communication between teachers and students. This a pproach serves to identify best practices and problems in the digitalization of the higher education system, and accelerate the digital transformation of educational institutions.